(untitled) - Jerry Martin Rosenberg (New York)
The book includes terms from accounting, administration, advertising, banking, business law, collective bargaining, commodities, distribution, economics, import-export, finance, government, insurance, labor relations, management, manufacturing, marketing, merchandising, operation research, organization, packaging, personnel, production, public administration, public policy, purchaging, research methodology, retailing, salesmanship, securities, shipping, stock market, transportation, and warehousing. Featuring over 7500 entries, this book captures business as it's conducted today. Many terms are used in different ways. The book closes with an appendix of useful tables
Keywords: business - dictionries,management - dictionaries